Fertility Preservation for Patients with Malignant Disease. Guideline of the DGGG, DGU and DGRM (S2k-Level, AWMF Registry No. 015/082, November 2017) – Recommendations and Statements for Girls and Women - Dittrich, Ralf; Kliesch, Sabine; Schüring, Andreas; Balcerek, Magdalena; Baston-Büst, Dunja M.; Beck, Ramona; Beckmann, Matthias W.; Behringer, Karolin; Borgmann-Staudt, Anja; Cremer, Wolfgang; Denzer, Christian; Diemer, Thorsten; Dorn, Almut; Fehm, Tanja; Gaase, Rüdiger; Germeyer, Ariane; Geue, Kristina; Ghadjar, Pirus; Goeckenjan, Maren; Götte, Martin; Guth, Dagmar; Hauffa, Berthold P.; Hehr, Ute; Hetzer, Franc; Hirchenhain, Jens; Hoffmann, Wilfried; Hornemann, Beate; Jantke, Andreas; Kentenich, Heribert; Kiesel, Ludwig; Köhn, Frank-Michael; Korell, Matthias; Lax, Sigurd; Liebenthron, Jana; Lux, Michael; Meißner, Julia; Micke, Oliver; Nassar, Najib; Nawroth, Frank; Nordhoff, Verena; Ochsendorf, Falk; Oppelt, Patricia G.; Pelz, Jörg; Rau, Beate; Reisch, Nicole; Riesenbeck, Dorothea; Schlatt, Stefan; Sender, Annekathrin; Schwab, Roxana; Siedentopf, Friederike; Thorn, Petra; Wagner, Steffen; Wildt, Ludwig; Wimberger, Pauline; Wischmann, Tewes; von Wolff, Michael; Lotz, Laura (Geburtshilfe und Frauenheilkunde, 2018)
Aim The aim of this official guideline published by the German Society of Gynecology and Obstetrics (DGGG) and coordinated with the German Society of Urology (DGU) and the German Society of Reproductive Medicine (DGRM) is to provide consensus-based recommendations, obtained by evaluating the relevant literature, on counseling and fertility preservation for prepubertal girls and boys as well as patients of reproductive age. Statements and recommendations for girls and women are presented below. Statements or recommendations for boys and men are not the focus of this guideline.Methods This S2k guideline was developed at the suggestion of the guideline commission of the DGGG, DGU and DGRM and represents the structured consensus of representative members from various professional associations (n = 40).Recommendations The guideline provides recommendations on counseling and fertility preservation for women and girls which take account of the patientʼs personal circumstances, the planned oncologic therapy and the individual risk profile as well as the preferred approach for selected tumor entities.Ziel Das Ziel dieser offiziellen Leitlinie, die von der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) publiziert und zusammen mit der Deutschen Gesellschaft für Urologie (DGU) sowie Deutschen Gesellschaft für Reproduktionsmedizin (DGRM) koordiniert wurde, ist es, durch die Evaluation der relevanten Literatur konsensbasierte Handlungsempfehlungen für die Beratung und den Einsatz von fertilitätserhaltenden Maßnahmen bei präpubertären Mädchen und Jungen sowie für Patienten/-innen im reproduktiven Alter zu geben. Im Folgendem werden die Statements und Empfehlungen für Mädchen und Frauen dargestellt. Die Statements und Empfehlungen für Jungen und Männer sind nicht Inhalt dieser Publikation.Methoden Diese S2k-Leitlinie wurde durch einen strukturierten Konsens von repräsentativen Mitgliedern verschiedener Fachgesellschaften (n = 40) im Auftrag der Leitlinienkommission der DGGG, DGU und DGRM entwickelt.Empfehlungen Es werden Empfehlungen zur Beratung und dem Einsatz von fertilitätserhaltenden Maßnahmen bei Patientinnen unter Berücksichtigung der Lebensumstände, der geplanten onkologischen Therapie und des individuellen Risikoprofils dargestellt sowie über das Vorgehen bei ausgewählten Tumorentitäten.
Keywords: fertility preservation; oncologic diseases; guideline